Tinjauan manajemen berbasis sekolah atas kontribusi supervisi pengawas sekolah, kepemimpinan kepala sekolah dan kinerja guru terhadap mutu pembelajaran guru pada SMA se-Kecamatan Tanimbar Selatan Kabupaten Maluku Tenggara Barat Provinsi Maluku - Maria Gorety Ametembun; Samsi Haryanto (Universitas Sarjanawiyata Tamansiswa, 2016)
The research aimed to know review of: the contribution of supervisor school Based Management of supervision contribution of school supervisor, principle leadership and teacher Performance to the quality of teacher learning (2) the contribution of supervision of school supervisor to the quality of teacher learning (3) the contribution of principle leadership to the quality of teacher learning (4) the contribution of teacher Performance to the quality of teacher learning. This research was conducted in high schools of South Tanimbar district, Regency of West Southeast Maluku, Province of Maluku. The Research method used was quantitative with survey method. Population in the research is all of the high school teachers either in public or public school at South Tanimbar district Regency of West Southeast Maluku, Province of Maluku as many 157 teachers. Sampling technique with proportional random sampling method as many as 110 teachers. Data of the research was collected by using questionnaire. The questionnaire was checked to see its validity and reliability tests. Data analysis used assumption test and multiple linear regression. The results of the research show that: (1) the supervision of school supervisor, principle leadership and teacher performance simultan normaly in together have positive influence significantly to the quality of teacher learning performance with the efectiveness contribution at 18,7% (2) the supervision of supervisor significantly has positive influence to the quality of teacher learning perfomence with the efectiveness contribution at 10,3% (3) the principle leadership significantly has positive influence to the quality of teacher learning perfomence with the efectiveness contribution at 5,6% (4) teacher performace significantly has positive influence to the quality of teacher learning perfomence with the efectiveness contribution at 6,0%. Principle who has a good leadership competency and school supervisor supervise intensively will make the implementation of the School-Based Management to be good and make teacher performance and the learning-teaching process to be good too.